1989
DOI: 10.1128/aem.55.12.3101-3106.1989
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Proteinase Release from Lactococcus lactis subsp. cremoris Wg2

Abstract: The procedure generally used for the isolation of extracellular, cell-associated proteinases of Lactococcus lactis species is based on the release of the proteinases by repeated incubation and washing of the cells in a Ca2+-free buffer. For L. lactis subsp. cremoris Wg2, as many as five incubations for 30 min at 29°C are needed in order to liberate 95% of the proteinase. Proteinase release was not affected by chloramphenicol, which indicates that release is not the result of protein synthesis during the incuba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0
1

Year Published

1990
1990
2001
2001

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(48 citation statements)
references
References 27 publications
(30 reference statements)
0
47
0
1
Order By: Relevance
“…In other words, free a S1 -casein could be less susceptible to the action of proteinase than when it is in a complex with other casein fractions. Release of lactococcal proteinase from the cell envelope was found to be an autoproteolytic event (Laan and Konings 1989;Haandrikman et al 1991). It was also found that Ca 2+ ions play an important role in maintaining the attachment of the enzyme to the cell.…”
Section: Discussionmentioning
confidence: 98%
“…In other words, free a S1 -casein could be less susceptible to the action of proteinase than when it is in a complex with other casein fractions. Release of lactococcal proteinase from the cell envelope was found to be an autoproteolytic event (Laan and Konings 1989;Haandrikman et al 1991). It was also found that Ca 2+ ions play an important role in maintaining the attachment of the enzyme to the cell.…”
Section: Discussionmentioning
confidence: 98%
“…Interestingly, the 80-kDa proteinase fragment was not only active, but also showed the same specificity towards casein as the larger enzyme ( [62][63][64]; see below). Recently, it was shown that an 87-kDa degradation product of the Wg2 proteinase still had the same N-terminal amino acid (Asp.188) as the largest proteinase band of 165 kDa present in this preparation, indicating that extensive C-terminal degradation had taken place [54].…”
Section: The Proteinase Modelmentioning
confidence: 92%
“…At the N-terminus a typical signal peptide-like sequence of 33 amino acids is present. The N-terminal amino acid sequences of the isolated proteinases have been determined and indicate that in all three cases the mature enzyme starts with the aspartic acid residue at position 188 of the predicted amino acid sequence [47,52,54].…”
Section: Homology With Subtilisinsmentioning
confidence: 99%
See 2 more Smart Citations